2020
DOI: 10.1007/s00428-020-02861-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of postmortem examination in the era of COVID-19 pandemic: the experience of a Northeast Italy University Hospital

Abstract: With the continuous spreading of SARS-CoV-2 and increasing number of deaths worldwide, the need and appropriateness for autopsy in patients with COVID-19 became a matter of discussion. In fact, in the COVID-19 era protection of healthcare workers is a priority besides patient management. No evidence is currently available about the real risk related to the procedure as well as to the subsequent management of the samples. We herein describe the procedure that has been used to perform the first series of postmor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 25 publications
4
33
1
5
Order By: Relevance
“…The first histopathologic reports of COVID-19-positive subjects were obtained from biopsies of alive patients, postmortem biopsies, surgical specimens, or transplanted organs [20,21,[47][48][49][50][51]. Evidence on the safety of postmortem examinations, if properly conducted, and positive/suspected SARS-CoV-2 corpse management recommendations have appeared [52][53][54][55][56][57][58], and some studies about complete autopsies of deceased SARS-CoV-2-positive patients have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first histopathologic reports of COVID-19-positive subjects were obtained from biopsies of alive patients, postmortem biopsies, surgical specimens, or transplanted organs [20,21,[47][48][49][50][51]. Evidence on the safety of postmortem examinations, if properly conducted, and positive/suspected SARS-CoV-2 corpse management recommendations have appeared [52][53][54][55][56][57][58], and some studies about complete autopsies of deceased SARS-CoV-2-positive patients have been published.…”
Section: Discussionmentioning
confidence: 99%
“…The features that allow us to count a decedent as a SARS-CoV-2 related death remain unclear. Many recommendations about the safety of autopsy procedures have been published [52][53][54][55][56][57][58], but to the best of our knowledge, an essential and standardized postmortem diagnostic tool for COVID-19 has not been proposed. As a consequence, the studies we reviewed show procedural differences, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, infectivity could only be determined using viral cultures [29], but this was unfortunately beyond the scope of the current study. Recently, vital virus could be transferred from lung samples from autopsies performed 6-day postmortem and cultivated in cell cultures but without reporting Ct values [30]. On the other hand, a recent correlation of Ct values with successful isolation of virus in cell cultures suggested that patients with Ct values above 33-34 were no longer contagious [31].…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem examination of COVID-19 should be performed in an autopsy suite, equipped if possible with a ventilation system with six complete air changes/h (ACH) in a pressurenegative environment, with air exhausted through HEPA filters [Biosafety Level 3 (BSL3)]. A detailed autopsy/sampling protocol has recently been published by the University of Padova Pathological Section [75]. The protocol requires that a video registration be taken during the autopsy.…”
Section: Autopsy/sampling Protocolmentioning
confidence: 99%